2010
DOI: 10.3844/ajbbsp.2010.116.119
|View full text |Cite
|
Sign up to set email alerts
|

Total Level of Serum Homocysteine in Males and Females with Coronary Heart Disease of Different Age Groups

Abstract: Problem statement: Elevated plasma total homocysteine concentration is a risk factor of cardiovascular disease. Total homocysteine level is a strong predictor of mortality in-patient with an angiographically confirmed Coronary Heart Disease (CHD), so we want to know at what age in males and females elevated homocysteine will be significantly elevated and this will help for better management and prognosis by decreasing the level of homocysteine. Approach: Plasma level of homocysteine was determined in male and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Symptoms of vitamin B12 deficiency include fatigue, weakness, anorexia, paresthesias, numbness and dizziness. Early diagnosis and prompt treatment of patients in the early stage of the disorder can often produce an improvement in their condition (Erickson et al, 2008;Melinda, 2006;Mohammad et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms of vitamin B12 deficiency include fatigue, weakness, anorexia, paresthesias, numbness and dizziness. Early diagnosis and prompt treatment of patients in the early stage of the disorder can often produce an improvement in their condition (Erickson et al, 2008;Melinda, 2006;Mohammad et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hcy, which mediates methionine metabolism, is catabolized in the reaction with the vitamin B6 cofactor of Cysteine (Cys). In most tissues, Hcy can be converted back to methionine by this re-methylation reaction, catalyzed by the enzyme "methionine synthase," requiring 5-methylene tetrahydrofolate (THF4) in the form of reduced folate as the methyl donor with vitamin B12 cofactor (Finkelstein et al, 2000;Ravaglia et al, 2005;Wijekoon et al, 2006;Ramakrishnan et al, 2006;Martinez et al, 2017;Mohammad et al, 2010;Kumar et al, 2017;Škovierová et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have shown that plasma Hcy concentrations increase with age (higher in adults than in pediatric periods), and are higher in males than females. It is known that the most important factors affecting Hcy level are genetic and nutritional factors (vitamin B6 and B12 or folate deficiencies), age, gender difference, physiological periods, especially the postmenopausal period and some metabolic disorders (Robinson et al, 1994;Mohammad et al, 2010;Piccione et al, 2008;Masuda et al, 2008;Škovierová et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Atherogenesis is affected by hemodynamic parameters, such as Wall Shear Stress (WSS), Wall Shear Stress Spatial Gradient (WSSG) and Oscillatory Shear Index (OSI) (Mohammad et al, 2010;Soulis et al, 2006;Huo et al, 2007;. These parameters are strongly influenced by flow disturbances, which are largely dependent on the geometry of arterial tree (Prosi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%